Government responses to the platform economy: where do we stand? - Lenaerts, Karolien; Beblavy, Miroslav; Kilhoffer, Zachary (Brussels, 2017)
"The introduction of the platform economy in Europe has sparked debate on the challenges it raises for workers, companies, social partners, governments and other stakeholders, and how these challenges can be addressed. This paper assesses government responses to the platform economy in seven EU countries: Belgium, Denmark, France, Germany, Hungary, Slovakia and Spain. It shows that, owing to the lack of a specific framework governing the platform economy, countries generally attempt to apply existing legislation, regulations and policies to the new challenges that the platform economy brings. This holds for the status of workers, working conditions, and industrial relations and social dialogue. Nevertheless, this strategy is not necessarily successful. The status of platform workers, for example, remains unclear in most member states. Some member states consider all platform workers to be self-employed, while in other member states, their status is much more dependent on the specific circumstances. There seems to be little debate on the idea of introducing a new status in the countries studied. On working conditions, the results confirm that most countries have applied the existing framework to platform work. In many of the member states, this has turned out to be problematic in several dimensions (e.g. taxation and social protection). In the area of industrial relations and social dialogue, there is much less evidence of specific actions or initiatives. This Policy Insight has been prepared as part of a research project entitled “IRSDACE – Industrial Relations and Social Dialogue in the Age of Collaborative Economy” for the European Commission. IRSDACE is a two-year project that sets out to examine how traditional players in the labour market, such as trade unions, employers' associations, member states and the EU, experience and respond to the platform economy."